Effects of Diminishing Problem-solving Prompts on Students’ Conceptual Understanding and Problem-solving Skills in Physics - Jugueta, Eleanor Alma D. (Alipato, A Journal of Basic Education; Vol 12 (2021): 25th Anniversary Issue, 2022)
This study investigated the effects of Diminishing Problem-solving Prompts (DPP) on students’ conceptual understanding and problem-solving skills in physics. It utilized a quasi-experimental pretest-post-test research design with two heterogenous intact classes. DPP was a teaching approach developed by the researcher using prompts during problem-solving tasks. A researcher-made Physics Achievement Test (PAT) was used to assess students’ conceptual understanding and problem-solving skills. To determine if the teaching approach was effective, the post-test scores were subjected to a one-tailed t-test for independent samples. The normalized gains of high- and low-performing students were also computed. Finally, the Pearson product-moment correlation was computed to assess the relationship between students’ conceptual understanding and problem-solving skills in physics. The statistical analyses showed that there was no significant difference between the mean post-test scores of the DPP and CP groups. Further analyses of the qualitative data suggested that high-performing DPP students exhibited expert-like behaviors in their problem-solving solutions. A strong positive correlation existed between students’ conceptual understanding and problem-solving skills in physics. Thus, the use of problem-solving strategies and prompts enhanced the conceptual understanding of students during problem-solving tasks. Further studies can be undertaken by using think-aloud interviews to investigate how students integrate physics concepts while solving problems using DPP. Keywords: problem-solving, problem-solving skills,  conceptual understanding, diminishing prompts,  achievement, physics education